Immune myocarditis related to sintilimab treatment in a patient with advanced lung adenocarcinoma: A case report - Lin, Yunling; Yuan, Xun; Chen, Lianglong (Frontiers in Cardiovascular Medicine, 2022)
Immune checkpoint inhibitors (ICI) have improved clinical outcomes of patients with advanced lung cancer, but may lead to fatal cardiac injury. We describe a 66-year-old man with advanced lung adenocarcinoma who presented with chest pain and dyspnea 3 weeks after the first dose of sintilimab. The initial electrocardiogram (ECG) demonstrated ST-elevation in leads V5-V9, and a high-sensitivity troponin level was significantly elevated. However, coronary angiography did not reveal any significant stenosis. The patient was successfully treated with methylprednisolone and immunoglobulin. Cardiac MRI was carried out before discharge and late gadolinium enhancement (LGE) was found to be in the mid layer of the septal segment and the subepicardial layer of the inferolateral wall. Due to the high fatality, ICI-related myocarditis requires close surveillance, prompt management and long-term follow-up.